The relationship between sexual health literacy and sexual function of women with diabetes mellitus: a cross-sectional study - Çakmak, Betül; Abay, Halime; Doğanay, Ceren Atilgan; Çelik, Nazan; Özel, Yasemin; Üstün, Yusuf (Oxford University Press (OUP), 2025)
Abstract Background Sexual dysfunction (SD) is a complication of poorly managed diabetes mellitus (DM). To prevent SD, patients should develop sexual health literacy (SHL). Objective This study investigated the relationship between SHL and SD in women with DM. Methods This cross-sectional study was performed between 1 October 2023 and 1 June 2024. The sample comprised 400 participants. The inclusion criteria were (1) being 18-65 years of age, (2) having been diagnosed with DM, and (3) having a sex partner. Data were collected using a personal information form, the Female Sexual Function Index (FSFI), and the Sexual Health Literacy Scale (SHLS). Outcomes The data were analyzed using the Mann–Whitney test, Kruskal–Wallis H test, Spearman correlation coefficients, and binary logistic regression. Results Over half of the participants experienced SD (68,2%). Participants with higher education, those whose partners had higher education, those who did not have any chronic disease other than DM, and those who did not take hormone replacement therapy had a lower rate of SD (P < 0.05). Participants with higher income, those who used family planning, those with DM I, and non-menopausal participants had lower SD and higher SHL (P < 0.05). Insulin-only participants had higher SD and lower SHL than those who were on other types of medications (P < 0.05). There was a significant negative correlation between scale scores (FSFI and SHLS) and age (r = -0.388; P < 0.001 r = -0.326; P < 0.001, respectively), age of partner (r = -0.383; P < 0.001, r = -0.274; P < 0.001, respectively), duration of romantic relationship (r = -0.326; P < 0.001, r = -0.328; P < 0.001, respectively), number of children (r = -0.109; P < 0.001, r = -0.290; P < 0.001, respectively), and duration of DM (r = -0.254; P < 0.001, r = -0.125; P < 0.013, respectively). There was a significant positive correlation between scale scores (FSFI and SHLS) and number of sexual intercourse (r = 0,493; P < 0.001, r = 0.127; P < 0.011, respectively). A one-unit increase in DM duration resulted in a 3.7% increase in SD rate (OR = 1.037). A one-unit increase in the number of sexual intercourses reduced the SD rate by 35.5% (OR = 0.645). Clinical Implication The data show that the prevalence of SD in diabetic women is directly affected by the number of sexual intercourses per week, menopausal status, and duration of DM. Strengths and limitations This is the first study to examine the relationship between SHL and SD in women with DM. Second, the results are sample-specific and cannot be generalized to all women with DM. Conclusion Healthcare professionals should ensure that women with DM have high levels of SHL to prevent SD and improve their quality of sexual life.
Keywords: Adult; Sexual Dysfunction, Physiological; Young Adult; Cross-Sectional Studies; Adolescent; Surveys and Questionnaires; Diabetes Mellitus; Humans; Female; Middle Aged; Sexual Health; Health Literacy; Aged